2010
DOI: 10.1016/j.jss.2009.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy with a Tumor-Targeting Mutant of S. typhimurium Inhibits Liver Metastasis in a Mouse Model of Pancreatic Cancer

Abstract: Cancer of the exocrine pancreas is the fourth leading cause of cancer deaths in the United States. Currently, surgical resection is the only hope for cure. The majority of patients present with locally advanced or metastatic disease. The most common site for distant metastasis is the liver. We report here a modified auxotrophic strain of S. typhimurium that can target and control the growth of liver metastasis in a mouse model of pancreatic cancer. This strain of S. typhimurium is auxotrophic (Leucine-arginine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 20 publications
1
80
0
Order By: Relevance
“…In fact, activation of TLR5 by commensal bacteria was shown to drive malignant progression at extramucosal locations through the promotion of inflammation, which dampened antitumor immunity by expanding immunosuppressive networks (65). In contrast, we and others have shown that TLR5 activation has tumor growth suppressive effects and stimulates antitumor immunity (19)(20)(21)(22)(23)(24)(25)(26)53). Earlier studies in our laboratory showed that entolimod displayed a growth-inhibitory effect on a TLR5-expressing mouse xenograft model of human lung adenocarcinoma A549 (23), supporting a direct effect of TLR5 stimulation on tumor growth suppression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, activation of TLR5 by commensal bacteria was shown to drive malignant progression at extramucosal locations through the promotion of inflammation, which dampened antitumor immunity by expanding immunosuppressive networks (65). In contrast, we and others have shown that TLR5 activation has tumor growth suppressive effects and stimulates antitumor immunity (19)(20)(21)(22)(23)(24)(25)(26)53). Earlier studies in our laboratory showed that entolimod displayed a growth-inhibitory effect on a TLR5-expressing mouse xenograft model of human lung adenocarcinoma A549 (23), supporting a direct effect of TLR5 stimulation on tumor growth suppression.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that the only known natural TLR5 agonist, flagellin, flagellin-expressing Salmonella bacteria, and a pharmacologically optimized flagellin derivative named entolimod (CBLB502) have antitumor effects in several tumor models (19)(20)(21)(22)(23), including mouse models of liver metastases (24)(25)(26). Moreover, systemic administration of TLR5 agonists is uniquely safe because of the restricted pattern of expression of TLR5 (primarily in the gut, liver, and bladder) and the nature of the cytokines induced following TLR5 stimulation.…”
mentioning
confidence: 99%
“…Second, the TLR5 agonist CBLB502 was shown to be effective as a tissue protectant in mouse models of renal ischemia-reperfusion injury (10). Third, bacterial flagellin and flagellin-expressing bacteria (Salmonella) have shown antitumor effects in mouse models of colon and liver metastasis of pancreatic cancer (11,12). Bacterial flagellin and its derivative, CBLB502, also demonstrated antitumor effects in several in vivo models (9,13,14).…”
mentioning
confidence: 99%
“…28 Leschner et al have observed a large influx of blood into the tumors by vascular disruption after treatment with S. typhimurium. Blood influx was followed by necrosis formation.…”
mentioning
confidence: 99%